A blended learning curriculum for training peer researchers to conduct community-based participatory research. (4th May 2018) - Eaton, Andrew D.; Ibáñez-Carrasco, Francisco; Craig, Shelley L.; Chan Carusone, Soo; Montess, Michael; Wells, Gordon A.; Ginocchio, Galo F.
ABSTRACT: Peer researchers (PRs) are research team members who share traits (e.g. gender, age, sexual orientation, diagnosis, income, housing situation, etc.) with study participants. Participatory methods and some fields (e.g. HIV/AIDS) expect PRs to be equitably involved in a project. Moreover, in Canada, there is a current impetus to include 'the patient' in health research. PRs often join a project without any formal research training, yet they are frequently tasked with suggesting appropriate language, recruiting participants, conducting interviews, administering surveys, analyzing data, and presenting findings. While there is literature on PR hiring, ethical considerations of PR engagement, and PR experiences, the methods of training PRs remain underreported. A blended learning curriculum (i.e. combination of webinars, didactic in-person presentation, filmed simulation, etc.), informed by the principles of action learning and the concept of reciprocity, has shown preliminary effectiveness in training PRs across two studies. This paper will present the curriculum, alongside exploratory evaluation results ( n  = 7), with details on how the curriculum changed from one study to the next and how reciprocity between academic and peer researchers led to stronger collaborations.